RUSSIA-EU CUSTOMS COOPERATION LEGAL BASE IN THE CONTEXT OF RUSSIA WTO ACCESSION - D. A. Turlanov (Vestnik MGIMO-Universiteta)
As a result of long-term accession process Russia became WTO member, which stipulates adequate analyze of relevant consequences both for Russia and its bilateral relations with trade partners. Taking into consideration the fact, that EU is Russia’s main trade partner and significant role of customs issues in ensuring smooth trade flows across the border, author provides legal assessment of Russia WTO accession influence on Russia-EU customs cooperation legal base. Author comes to the conclusion that due to trade, but not customs nature WTO addresses customs to prevent it from being obstacle to trade. Besides, during accession process Russia in general provided correspondence of its legislation to WTO norms. For example, Russia-EU customs cooperation is based on WTO norms from the date of Partnership and Cooperation Agreement entering into force, in which included references on General Agreement on Tariff and Trade. These facts minimize Russia WTO accession influence on the process of Russia-EU customs cooperation legal base construction. At the same time author proves Russia-EU customs cooperation instrument fruitfulness in elimination of risks arising from Russia WTO accession. Such instruments will support effective customs administration without unreasonable interference in trade flows, including within WTO. At the same time it will be important factor for economic, national security as well as for increase of investment attractiveness of Russia.